Stereochemistry and innate immune recognition: (+)‐norbinaltorphimine targets myeloid differentiation protein 2 and inhibits toll‐like receptor 4 signaling. Issue 8 (4th June 2019) - Zhang, Xiaozheng; Peng, Yinghua; Grace, Peter M.; Metcalf, Matthew D.; Kwilasz, Andrew J.; Wang, Yibo; Zhang, Tianshu; Wu, Siru; Selfridge, Brandon R.; Portoghese, Philip S.; Rice, Kenner C.; Watkins, Linda R.; et al.
ABSTRACT: Deregulation of innate immune TLR4 signaling contributes to various diseases including neuropathic pain and drug addiction. Naltrexone is one of the rare TLR4 antagonists with good blood‐brain barrier permeability and showing no stereoselectivity for TLR4. By linking 2 naltrexone units through a rigid pyrrole spacer, the bivalent ligand norbinaltorphimine was formed. Interestingly, (+)‐norbinaltorphimine [(+)‐1] showed ∼25 times better TLR4 antagonist activity than naltrexone in microglial BV‐2 cell line, whereas (–)‐norbinaltorphimine [(–)‐1] lost TLR4 activity. The enantioselectivity of norbinaltorphimine was further confirmed in primary microglia, astrocytes, and macrophages. The activities of meso isomer of norbinaltorphimine and the molecular dynamic simulation results demonstrate that the stereochemistry of (+)‐1 is derived from the (+)‐naltrexone pharmacophore. Moreover, (+)‐1 significantly increased and prolonged morphine analgesia in vivo . The efficacy of (+)‐1 is long lasting. This is the first report showing enantioselective modulation of the innate immune TLR signaling.—Zhang, X., Peng, Y., Grace, P. M., Metcalf, M. D., Kwilasz, A. J., Wang, Y., Zhang, T., Wu, S., Selfridge, B. R., Portoghese, P. S., Rice, K. C., Watkins, L. R., Hutchinson, M. R., Wang, X. Stereochemistry and innate immune recognition: (+)‐norbinaltorphimine targets myeloid differentiation protein 2 and inhibits toll‐like receptor 4 signaling. FASEB J. 33, 9577‐9587 (2019). www.fasebj.org